The supplementation of a high dose of fish oil during pregnancy and lactation led to an elevation in Mfsd2a expression without any changes in docosahexaenoic acid levels in the retina of healthy 2-month-old mouse offspring - Macura, Irena Jovanovic; Djuricic, Ivana; Major, Tamara; Milanovic, Desanka; Sobajic, Sladjana; Kanazir, Selma; Ivkovic, Sanja (Frontiers in Nutrition, 2024)
Introduction During fetal development, the proper development of neural and visual systems relies on the maternal supplementation of omega-3 fatty acids through placental transfer. Pregnant women are strongly advised to augment their diet with additional sources of omega-3, such as fish oil (FO). This supplementation has been linked to a reduced risk of preterm birth, pre-eclampsia, and perinatal depression. Recently, higher doses of omega-3 supplementation have been recommended for pregnant women. Considering that omega-3 fatty acids, particularly docosahexaenoic acid (DHA), play a crucial role in maintaining the delicate homeostasis required for the proper functioning of the retina and photoreceptors the effects of high-dose fish oil (FO) supplementation during pregnancy and lactation on the retina and retinal pigmented epithelium (RPE) in healthy offspring warrant better understanding. Methods The fatty acid content and the changes in the expression of the genes regulating cholesterol homeostasis and DHA transport in the retina and RPE were evaluated following the high-dose FO supplementation. Results Our study demonstrated that despite the high-dose FO treatment during pregnancy and lactation, the rigorous DHA homeostasis in the retina and RPE of the two-month-old offspring remained balanced. Another significant finding of this study is the increase in the expression levels of major facilitator superfamily domain-containing protein (Mfsd2a), a primary DHA transporter. Mfsd2a also serves as a major regulator of transcytosis during development, and a reduction in Mfsd2a levels poses a major risk for the development of leaky blood vessels. Conclusion Impairment of the blood-retinal barrier (BRB) is associated with the development of numerous ocular diseases, and a better understanding of how to manipulate transcytosis in the BRB during development can enhance drug delivery through the BRB or contribute to the repair of central nervous system (CNS) barriers.